2022
DOI: 10.3390/ijerph20010200
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Electronic Medical Record Driven Quality Measurement and Feedback Systems

Abstract: Historically, quality measurement analyses utilize manual chart abstraction from data collected primarily for administrative purposes. These methods are resource-intensive, time-delayed, and often lack clinical relevance. Electronic Medical Records (EMRs) have increased data availability and opportunities for quality measurement. However, little is known about the effectiveness of Measurement Feedback Systems (MFSs) in utilizing EMR data. This study explores the effectiveness and characteristics of EMR-enabled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 61 publications
0
10
0
Order By: Relevance
“…Our finding that some companies are promoting pharmaceutical products through virtual care platforms by adjusting patient care pathways is worrisome as it permits industry to directly influence clinical care 98. Adjusting patient care pathways and evaluating the impact on quality of care has the potential to improve health outcomes 99–102. However, studies show that pharmaceutical industry influence over medical care prioritises a company’s commercial objectives rather than quality patient care and has caused substantial patient harm 56 98 103–106…”
Section: Discussionmentioning
confidence: 99%
“…Our finding that some companies are promoting pharmaceutical products through virtual care platforms by adjusting patient care pathways is worrisome as it permits industry to directly influence clinical care 98. Adjusting patient care pathways and evaluating the impact on quality of care has the potential to improve health outcomes 99–102. However, studies show that pharmaceutical industry influence over medical care prioritises a company’s commercial objectives rather than quality patient care and has caused substantial patient harm 56 98 103–106…”
Section: Discussionmentioning
confidence: 99%
“…It is well-documented that the impact of measurement feedback systems is variable 5 6. These interviews highlighted that while there is a lack of published evidence providing consistent and definitive correlations to improved quality of care and patient outcomes, rich information exists in expert knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…However, the effectiveness was variable and dependent on factors, including the feedback recipients’ baseline performance and how the feedback is provided 5. Despite data collection and technology advances over the last decade, the translation and impact of measurement feedback systems on patient outcomes and quality of care remain inconsistent 5 6. In 2019, Grimshaw et al suggested that future research should focus on how, when and why measurement feedback systems are most effective,7 as the literature often lacks implementation context and feedback processes 6 8.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations